Tingkat Pengetahuan Agama Penonton Tayangan Buya Yahya Menjawab pada Channel Youtube Al-Bahjah TV di Masa Pandemi COVID-19 - Oftaviani, Sri; Negoro, Noor Bekti (Jurnal Penyuluhan Agama, 2022)
Abstract: The use of the internet and social media during the pandemic is a solution in various activities. The We are social Hootsuite data (2021), shows that YouTube is the most frequently accessed social media by Indonesians with the percentage of Youtube (93.8%), then Whatsapp (87.7%), Instagram (86.6%), and Facebook (85). ,5%). This phenomenon is seen as a great opportunity to be able to carry out religious education through YouTube social media. The YT Al-Bahjah TV channel is one of the da'wah channels that takes advantage of this opportunity to conduct religious counseling. The purpose of this research; (1) describe the characteristics of the audience of Buya Yahya Answers show (2) describe the level of religious knowledge of the audience of Buya Yahya Answers show (3) analyze the influence between Religious Counseling and the religious knowledge of the audience of Buya Yahya Answers. This research uses a quantitative approach with a survey method. The number of samples in this study was 100 people. The data analysis used was the classical assumption test, multiple linear regression test, correlation coefficient test and determination, t test (partial) and F test (simultaneous). The results of this study indicate that (1) the majority of respondents are 15-28 years old, while the majority of respondents have their last bachelor's degree in addition to that the majority of research respondents are female and the majority of respondents have one gadget, (2) the level of religious knowledge of viewers of Buya Yahya's shows. Al-Bahjah TV's youtube channel is in the high category with a percentage of 45.54 percent, and (3) there is an influence between religious counseling and religious knowledge of viewers of Buya Yahya Answers' show on the Al-Bahjah TV youtube channel with a percentage of 39.1 percent.Abstrak: Pemanfaatan internet dan media sosial di masa pandemi menjadi solusi dalam berbagai kegiatan. Data We are social Hootsuite (2021), menunjukkan bahwa media sosial youtube paling sering diakses masyarakat Indonesia dengan persentase Youtube (93,8%), kemudian Whatsapp (87,7%), instagram (86,6%), dan Facebook (85,5%). Fenomena tersebut dipandang sebagai peluang besar untuk dapat melakukan penyuluhan agama melalui media sosial youtube. Channel YT Al-Bahjah TV adalah salah satu channel dakwah yang memanfaatkan peluang tersebut untuk melakukan penyuluhan agama. Penelitian ini bertujuan; (1) mendeskripsikan karakteristik penonton tayangan Buya Yahya Menjawab (2) mendeskripsikan tingkat pengetahuan agama penonton  tayangan Buya Yahya Menjawab (3) menganalisis pengaruh antara Penyuluhan Agama dengan pengetahuan agama penonton tayangan Buya Yahya Menjawab. Peneltian ini menggunakan pendekatan kuantitatif dengan metode survei. Jumlah sampel penelitian ini sebanyak 100 orang Analisis data yang digunakan adalah uji asumsi klasik, uji regresi linear berganda, uji koefisien korelasi dan determinasi, uji t (parsial) dan uji F (simultan). Hasil penelitian ini menunjukkan bahwa (1) mayoritas usia responden adalah 15-28 tahun sedangkan mayoritas responden menempuh pendidikan terakhir S1 selain itu responden penelitian mayoritas berjenis kelamin perempuan dan mayoritas responden memiliki satu gadget, (2) tingkat pengetahuan agama penonton tayangan Buya Yahya Menjawab pada channel youtube Al-Bahjah TV berkategori tinggi dengan persentase 45,54 persen, dan (3) terdapat pengaruh antara penyuluhan agama dengan pengetahuan agama penonton tayangan Buya Yahya Menjawab pada channel youtube Al-Bahjah TV dengan persentase sebesar 39,1 persen.